2014
DOI: 10.1016/j.scitotenv.2013.12.065
|View full text |Cite
|
Sign up to set email alerts
|

A review on the occurrence of micropollutants in the aquatic environment and their fate and removal during wastewater treatment

Abstract: Micropollutants are emerging as a new challenge to the scientific community. This review provides a summary of the recent occurrence of micropollutants in the aquatic environment including sewage, surface water, groundwater and drinking water. The discharge of treated effluent from WWTPs is a major pathway for the introduction of micropollutants to surface water. WWTPs act as primary barriers against the spread of micropollutants. WWTP removal efficiency of the selected micropollutants in 14 countries/regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
1,575
4
78

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 3,256 publications
(1,832 citation statements)
references
References 182 publications
42
1,575
4
78
Order By: Relevance
“…They pose a threat to ecological security and human health by interfering with endocrine system even at concentrations as low as ng·L −1 level [5]. It has been reported that 0.1 ng·L −1 EE2 could induce male rainbow trout to produce vitellogenin, which is only found in female rainbow trout, thus resulting in homozygosity of male and female trout [6]. In addition, EDCs can cause the growth retardation of sea urchin embryos.…”
Section: Introductionmentioning
confidence: 99%
“…They pose a threat to ecological security and human health by interfering with endocrine system even at concentrations as low as ng·L −1 level [5]. It has been reported that 0.1 ng·L −1 EE2 could induce male rainbow trout to produce vitellogenin, which is only found in female rainbow trout, thus resulting in homozygosity of male and female trout [6]. In addition, EDCs can cause the growth retardation of sea urchin embryos.…”
Section: Introductionmentioning
confidence: 99%
“…As for the other classes of PCPs, Luo, et al [28] when studying the occurrence of micropollutants in aquatic environment, concluded that galaxolide and tonalide were the most frequent musks in influents showing concentrations of 0.12 to 97 nM. Triclosan for antimicrobials and benzophenone-3 for organic UV filters were found in concentrations ranging from 0.10 to 83 and 0.43 to5 nM, respectively [28].…”
Section: Mip Synthesis For Personal Care Productsmentioning
confidence: 99%
“…To our knowledge the antibiotics within this study are not provided in a prodrug form, making estimates of their usage susceptible to misinterpretation owing to potential improper disposal. The recalcitrance of antibiotics is known to vary greatly in wastewater [44,45] making it considerably more difficult to accurately predict environmental concentrations, as can been seen in Table 3. The variability in the recalcitrance of antibiotics in WWTPs and within the same WWTP over time and between differing WWTPs of different size and treatment technologies are likely among the main sources of error in the wastewater epidemiology approach when applied to antibiotics.…”
Section: Pharmaceutical Occurrence In the Thames River Catchmentmentioning
confidence: 99%